THE CONTRIBUTION OF MUKMIN MANDIRI PESANTREN IN THE ACHIEVEMENT OF SUSTAINABLE DEVELOPMENT GOALS (SDGs) THROUGH POVERTY ALLEVIATION - Safika Rosyidatul Arifah; Irham Zaki (Universitas Airlangga, 2020)
UN member states have carried out a series of sustainable development in 2030 and included 17 Sustainable Development Goals (SDGs). One of the main points of attention is the first point concerning poverty alleviation which is largely due to unemployment. Therefore we need an effective strategy in solving these problems. Not only from the government, but can also come from the community. Similarly, pondok pesantren. With the existence of pesantren, the government strongly believes that pesantren can improve welfare and alleviate poverty. One of the pesantren involved is the Mukmin Mandiri boarding school, which also contributes to the economic development of the people, namely unemployment reduction, by empowering the community to become students having religious provisions as well as entrepreneurs through opening employment opportunities for students. The purpose of this study is to determine the role of pesantren in poverty alleviation. The research method used is qualitative with a case study design. Data collected through observation, interviews and documents. Then, the data is validated by triangulation of sources and techniques. The results showed the existence of pesantren businesses as a way of opportunity and a place for empowering skills for unemployed people. Furthermore, the empowerment of these skills can be reflected in the recognition of the background of the santri.Keywords: Pesantren Economy, Sustainable Development Goals, poverty alleviation, unemployment skills empowerment